2019
DOI: 10.1016/j.jvacx.2019.100032
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the cost per child vaccinated with full versus fractional-dose inactivated poliovirus vaccine

Abstract: Introduction Inactivated poliovirus vaccine (IPV) shortages and evidence of improved immunogenicity of two intradermal (ID) fractional IPV (fIPV) doses compared with one full intramuscular dose led to recommendations for fIPV delivery. To provide evidence on the economics of fIPV, we estimated the cost per child vaccinated using full-dose IPV compared with fIPV in routine and campaign settings. We evaluated the impact on costs of alternative devices facilitating ID administration, vaccine vial siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Questions also remain about the formulations of IPV vaccine that may become available in the future, which will affect future poliovirus vaccine policy modeling and the path of the polio endgame [240]. Currently, most OPV-using countries deliver stand-alone formulations of IPV, although in some cases they use off-label fractional intradermal delivery, which can save substantially on antigen costs, but cost more with respect to administration [230]. Research underway may also provide an IPV vaccine patch option [242][243][244][245], which would potentially achieve both dose-sparing of IPV and ease of delivery that could increase coverage, albeit at a potentially higher and uncertain cost.…”
Section: Expert Opinionmentioning
confidence: 99%
See 1 more Smart Citation
“…Questions also remain about the formulations of IPV vaccine that may become available in the future, which will affect future poliovirus vaccine policy modeling and the path of the polio endgame [240]. Currently, most OPV-using countries deliver stand-alone formulations of IPV, although in some cases they use off-label fractional intradermal delivery, which can save substantially on antigen costs, but cost more with respect to administration [230]. Research underway may also provide an IPV vaccine patch option [242][243][244][245], which would potentially achieve both dose-sparing of IPV and ease of delivery that could increase coverage, albeit at a potentially higher and uncertain cost.…”
Section: Expert Opinionmentioning
confidence: 99%
“…Finally, the search captured a 2017 study that reported on the GPEI costs associated with supporting tOPV-using countries as they switched to bOPV [ 179 ]. The search did not capture a 2019 study that reported the cost per child vaccinated with full versus fractional-dose IPV [ 230 ].…”
Section: Summary Of Publications Reviewedmentioning
confidence: 99%
“…In addition, the use of needles and syringes for administration was associated with the potential for needle re-use. Over past decades, there have been efforts to develop and implement new vaccine-product innovations to overcome some of these delivery and administration barriers and four are described in these case studies ( Box 1 , Box 2 , Box 3 , Box 4 , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [17] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [15] , [16] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] ).…”
Section: The Retrospective Innovation Environment: Four Vaccine-product Innovation Case Studiesmentioning
confidence: 99%
“…The historical cost estimates for poliovirus vaccines in Table I do not account for some of the products that have entered or may enter the market. In addition, for prospective health economic analyses, we also recognize the opportunity to make adjustments based on updated price estimates from the UNICEF supply division (UNICEF, 2019), policies that affect wastage assumptions (World Health Organization, 2014b), information about the costs of new products (Leo, 2019; Mvundura et al., 2019), and the need to consider the implications of updated guidelines and recommendations (World Health Organization, 2019b).…”
Section: Polio Vaccine Cost and Valuation Input Estimatesmentioning
confidence: 99%
“…Table I summarizes estimates of polio vaccine cost and valuation inputs for different income levels based on prior analyses and useful for retrospective economic analyses for 1988-2018(Duintjer Tebbens & Thompson, 2016Duintjer Tebbens et al, 2011;Duintjer Tebbens, Pallansch, Wassalik, et al, 2015;Duintjer Tebbens, Sangrujee, & Thompson, 2006;Thompson & Duintjer Tebbens, 2014;Thompson et al, 2008) Thompson, 2016;Duintjer Tebbens et al, 2011;Duintjer Tebbens, Pallansch, et al, 2006;Duintjer Tebbens, Pallansch, Wassalik, et al, 2015;Thompson & Duintjer Tebbens, 2014;Thompson et al, 2008 The historical cost estimates for poliovirus vaccines in Table I do not account for some of the products that have entered or may enter the market. In addition, for prospective health economic analyses, we also recognize the opportunity to make adjustments based on updated price estimates from the UNICEF supply division (UNICEF, 2019), policies that affect wastage assumptions (World Health Organization, 2014b), information about the costs of new products (Leo, 2019;Mvundura et al, 2019), and the need to consider the implications of updated guidelines and recommendations (World Health Organization, 2019b).…”
Section: Polio Vaccine Cost and Valuation Input Estimatesmentioning
confidence: 99%